SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMA BERAS UNTUK KELUARGA MISKIN (RASKIN) PADA KELURAHAN LESANE KECAMATAN KOTA MASOHI KABUPATEN MALUKU TENGAH DENGAN MENGGUNAKAN METODE WP (WEIGHTED PRODUCT) - Cici Irmawati Tukan; Sujito; Mochamad Husni (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2023)
Raskin is a conditional food aid program organized by the Government of Indonesia in selling rice at below market prices to specific recipients. In an effort to help the poor people which reached 28.07 million / soul. Since January 2003 the government issued RASKIN program. Village of Lesane has implemented RASKIN government program for poor families that began in 2003, but still found obstacles in the implementation of which is still using the conventional system. The method used for sorting is Weighted Product is part of the concept of Multi-Attibut Decision Making (MADM) where necessary normalization calculation. The concept of development of this system to apply the cycle System Development Life Cycle (SDLC). The results obtained by the accuracy rate of 100%